Calcium-catalysed synthesis of amines through imine hydrosilylation: an experimental and theoretical study. Issue 5 (10th January 2023) - Boumekla, Yougourthen; Xia, Fengjie; Vidal, Lucas; Totée, Cédric; Raynaud, Christophe; Ouali, Armelle
Abstract : Ca(NTf2 )PF6, generated from commercial precursors, promotes imine hydrosilylation in high yields and is used to prepare a bioactive amine on the gram scale. The mechanistic investigations highlight an unprecedented Si–H activation by the Ca center. Abstract : A method to reduce aldimines through hydrosilylation is reported. The catalytic system involves calcium triflimide (Ca(NTf2 )2 ) and potassium hexafluorophosphate (KPF6 ) which have been shown to act in a synergistic manner. The expected amines are obtained in fair to very high yields (40–99%) under mild conditions (room temperature in most cases). To illustrate the potential of this method, a bioactive molecule with antifungal properties was prepared on the gram scale and in high yield in environmentally friendly 2-methyltetrahydrofuran. Moreover, it is shown in this example that the imine can be prepared in situ from the aldehyde and the amine without isolating the imine. The mechanism involved has been explored experimentally and through DFT calculations, and the results are in accordance with an electrophilic activation of the silane by the calcium catalyst.